Analisis Pengaruh Kurs, Inflasi, Cadangan Devisa Terhadap Ekspor Di Indonesia Tahun 1992–2021 - Sapeni Sapeni; Sarmila Sarmila; Aly Hanafiyan (AKUNTANSI 45, 2023)
This research is entitled the influence of exchange rates, inflation, foreign exchange reserves on exports in Indonesia in 1992 -2021. This study aims to study how exports develop in Indonesia and review whether there is a relationship between exchange rates and exports. The data used are secondary data and time series data obtained from the World Bank Data Indonesia, using the VAR (Vector Auto Regression) analysis method using the E-Views 10 application. The results of the analysis in this study are that exchange rate variables have a large relationship to the export variable is compared to the inflation variable and the foreign exchange reserve variable